2003
DOI: 10.1002/art.10923
|View full text |Cite
|
Sign up to set email alerts
|

Isometric muscle force measurement for clinicians treating patients with osteoarthritis of the knee

Abstract: Objective. To evaluate the discriminant validity and, for clinicians, the test-retest reliability of isometric force in patients with knee osteoarthritis (OA). Methods. Mean isometric muscle strength data collected for 113 patients with knee OA were compared with published normative data for 131 asymptomatic subjects. Results. Patients with knee OA, ages 60 -79 years, could attain only 40 -53% of the knee extensor force and 35-46% of the knee flexor force generated by their age-and sex-matched peers. One-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 35 publications
(36 reference statements)
5
34
1
3
Order By: Relevance
“…3,28 This level may be an appropriate target for deciding whether or not intervention is warranted to slow or even avoid the development of medial compartment OA. Second, clinicians should consider conservative interventions such as strengthening of the quadriceps 29,30 and iliotibial band 31,32 or gait retraining 33,34 to lower the adduction torque to below the target level. For example, a medial thrust gait motion designed in a recent computational study has been shown to reduce the peak adduction torque by 35-50%, 35 an amount comparable to HTO surgery, in the one patient studied thus far.…”
Section: Discussionmentioning
confidence: 99%
“…3,28 This level may be an appropriate target for deciding whether or not intervention is warranted to slow or even avoid the development of medial compartment OA. Second, clinicians should consider conservative interventions such as strengthening of the quadriceps 29,30 and iliotibial band 31,32 or gait retraining 33,34 to lower the adduction torque to below the target level. For example, a medial thrust gait motion designed in a recent computational study has been shown to reduce the peak adduction torque by 35-50%, 35 an amount comparable to HTO surgery, in the one patient studied thus far.…”
Section: Discussionmentioning
confidence: 99%
“…For each of the two muscle groups, the highest obtained value (in N) of three consecutive trials was defined as the maximal isometric force. A comparable isometric strength testing device has been shown to demonstrate discriminant validity and high test-retest reliability in knee OA patients [22].…”
Section: Potentially Modifiable Physical Factors Measurementsmentioning
confidence: 99%
“…Thigh muscle weakness has been commonly observed in patients with knee osteoarthritis (KOA) (1)(2)(3)(4)(5) or knee pain (6,7), and low muscle strength has been associated with incident symptomatic, but not with incident radiographic KOA (8). Muscle weakness is considered a potentially modifiable (9) risk factor of KOA and quadriceps muscle strengthening is recommended by the current Osteoarthritis Research Society International KOA treatment guidelines (10).…”
Section: Introductionmentioning
confidence: 99%